Beijerinckia fluminensis BFC-33, a novel multi-stress-tolerant soil bacterium: Deciphering the stress amelioration, phytopathogenic inhibition and growth promotion in Triticum aestivum (L.). (May 2022) - AL-Shwaiman, Hind A.; Shahid, Mohammad; Elgorban, Abdallah M.; Siddique, Kadambot H.M.; Syed, Asad
Abstract: Environmental challenges like drought, salinity, heavy metals and pesticides directly/indirectly influence the environment and decreased the agricultural output. During its long developmental stages, cereal crops including wheat is exposed to a variety of abiotic/biotic stressors. Certain beneficial soil bacteria that can ameliorate environmental stresses can be exploited as crop growth promoters/enhancers under adverse situations. In this study, Beijerinckia fluminensis BFC-33 (accession no. MT672580) isolated from potato rhizosphere tolerated variousabiotic (drought, salinity, temperature, heavy metals, and fungicides) stresses. Strain BFC-33 demonstrated multifarious plant-growth-promoting (PGP) characteristics, such as the production of indole-3-acetic acid, P-solubilization, ACC deaminase, ammonia, siderophore, HCN, EPS, and extracellular enzymes. The antagonistic potential of BFC-33 against major fungal pathogens was ranked: Alternaria alternata (79.2%)> Rhizoctonia solani (69%)> Fusarium oxysporum (23.5%)> Ustilaginoidea virens (17%). Furthermore, bacterization of wheat seeds witha multi-stress-tolerant strain revealed B. fluminensis as a plant growth enhancer and biocontrol agent. For instance, increase in root length (cm) in BFC-33 inoculated wheat exposed to abiotic and biotic stresses at the seedling stage was ranked: B. fluminensis (24.2) >B. fluminensis + 100μgTBZLmL −1 (21.3) = B. fluminensis + 2%PEG (21.3) >B. fluminensis + 100 mM NaCl (19.7) >B. fluminensis + 100μgPbmL −1 (19) = B. fluminensis 100μgMNZBmL −1 (19)> B. fluminensis + A. alternata (17.4)> B. fluminensis + 100μgCdmL −1 (17)> B. fluminensis + F. oxysporum (13.4). In addition, increase in carotenoid accumulation (mg g −1 FW) in the foliage of BFC-33 inoculated wheat exposed to fungal infection was ranked: BFC-33 (3.88) > BFC-33+ A. alternata (3.0)>BFC-33+ R. solani (2.78) > BFC-33+ F. oxysporum (2.44). Moreover, BFC-33 inoculation significantly ( p ≤ 0.05) reduced stress-induced stressor molecules (proline and TBARS) and electrolyte leakage. Furthermore, B. fluminensis BFC-33 potentially enhanced the defense responses in wheat seedlings by increasing phenylalanine ammonia lyase (PAL), β-1, 3 glucanase, and polyphenol oxidase (PPO), which play a significant role in protecting plants from phytopathogens. Even so, by successfully establishing a product with the requisite effects under field settings, selecting multi-stress-tolerant and antagonistic plant growth promoting rhizobacteria (PGPRs) would be helpful to end-users. Future use of native multi-stress-tolerant bacteria as biocontrol agents in conjunction with existing drought, salinity, heavy metal, and pesticide tolerance might contribute to global food security. Graphical abstract: Image 1 Highlights: Beijerinckia fluminensis BFC-33, a multi-stress tolerant PGPR exhibited the antagonistic response against fungal pathogens. Under both abiotic and biotic stresses, BFC-33 improved the germination efficiency, growth, biomass and photosynthetic pigments in Triticum aestivum (L.) B. fluminensis BFC-33 lowered the stress markers and oxidative damage. Antioxidant enzymes in stressed-wheat seedling increased following B. fluminensis BFC-33 inoculation. BFC-33 potentially enhanced defense responses against phytopathogens by increasing phenylalanine ammonia lyase (PAL), β-1, 3 glucanase and polyohenol oxidase (PPO).